Angola : Staff Report for the 2004 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2005)
This 2004 Article IV Consultation highlights that Angola's GDP grew by 11 percent in 2004, following a slowdown in growth in 2003, largely reflecting the profile of oil production, which now accounts for one-half of GDP. The economy outside the extractive sector is currently estimated to be growing by about 9 percent. Despite extensive landmines and devastated infrastructure, agricultural production has recently begun to recover. Progress on structural reform and the implementation of policies to deal systematically with poverty reduction has been limited. The state continues to exercise a heavy influence in many sectors.